N400 predicts recovery from disorders of consciousness. Issue 5 (26th February 2013) - Steppacher, Inga; Eickhoff, Simon; Jordanov, Todor; Kaps, Michael; Witzke, Wolfgang; Kissler, Johanna
<x xml:space="preserve">Abstract</x> Objective Patients with the unresponsive wakefulness syndrome (UWS; formerly vegetative state) or in a minimally conscious state (MCS) open their eyes spontaneously but show no (UWS) or only marginal (MCS) signs of awareness. Because these states can become permanent, residual information processing capacities need to be determined, and reliable outcome predictors need to be found. We assessed higher‐order cortical information processing in UWS or MCS in a large group of patients using electroencephalographic event‐related potentials (ERPs) and determined their long‐term prognostic value for recovery. Methods Cognitive ERPs elicited by sound (P300) and speech (N400) were used to assess information processing in 92 behaviorally unresponsive patients diagnosed as in the state of either UWS (n=53) or MCS (n=39). ERPs were assessed with a clinical standard evaluation method and a computerized method, the t‐continuous wavelet transform. The patients' clinical outcome was followed up between 2 and 14 years after discharge from the rehabilitation center. Results Within the first year of the disease, many patients showed an intact P300 and several also an N400, indicating considerable residual information processing. At clinical follow‐up, about 25% of the patients recovered and regained communicative capabilities. A highly significant relationship between N400, but not P300, presence and subsequent recovery was found. Interpretation Results specify cognitive capabilities in disorders of consciousness, and determine their prognostic value. Specifically the N400 ERP is suggested as an important tool to assess information‐processing capacities that can predict the likelihood of recovery of patients in UWS or MCS. Ann Neurol 2013;73:594–602